Anti-Mullerian hormone (AMH) as a predictor of antral follicle population in heifers - Tavares Cardoso, Christopher Junior; Oliveira Junior, Jair Sabio de; Kischel, Henrique; Leite da Silva, Wilian Aparecido; Silva Arruda, Elielton Dias da; Souza-Caceres, Mirela Brochado; Mendes de Oliveira, Fernanda Amarante; Nogueira, Eriklis; Nogueira, Guilherme de Paula [UNESP]; Melo-Sterza, Fabiana de Andrade (Brazilian Coll Animal Reproduction, 2018)
Antral follicular population (AFP) and anti-Mullerian hormone (AMH) concentration are strongly associated. Thus, analyzing AMH concentration is a reliable method to predict animals with high AFP, an important feature to select donor cows for embryos and oocytes. However, not much is known about this parameter in heifers, particularly in crossbred animals. The aim of this study was to assess AFP in heifers and cows and its relation to serum AMH levels. Bos taurus indicus cows (36-60-months-old; n = 30) and heifers (12-14-months-old; n = 17) of the same breed were evaluated. A single procedure of follicular counting was performed by ultrasound for each animal. Random sampling was performed to analyze serum AMH concentration. Cows showed higher AFP than heifers; nonetheless, plasma AMH concentration did not differ between the categories. A high correlation of AFP with plasma AMH concentration was observed in Girolando heifers. Thus, it is suggested that AMH concentration could be a reliable and less invasive method for selecting heifers with high AFP.
Keywords: bovine; follicles; selection donors